Exploring the Experience and Insights of Chinese Registered Nurses on Alternative Medicine - Chen, Hui (International Journal of Public Health and Medical Research, 2024)
This study explores the perceptions and experiences of Chinese registered nurses regarding the clinical use of alternative medicine. The research focuses on nurses from various departments and roles, including specialist nurses, clinical nurses, and nursing management personnel. Through interviews, participants share their experiences, challenges, and views on alternative medicine in their daily work. The data collected will be analyzed using the Collaizi method. The study identifies four main themes: the development of alternative medicine in China, the challenges faced by nurses, how they overcome these challenges, and their predictions for the future of alternative medicine in the country. Key findings highlight the emotional impact of work changes, the difficulties encountered in the nursing profession, and nurses’ resilience. Lastly, participants offer insights into the future of alternative medical practices in China.